2017
DOI: 10.4236/ojs.2017.75062
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Existing Biased Estimators and the Respective Predictors in a Misspecified Linear Regression Model

Abstract: In this paper, the performance of existing biased estimators (Ridge Estimator (RE), Almost Unbiased Ridge Estimator (AURE), Liu Estimator (LE), Almost Unbiased Liu Estimator (AULE), Principal Component Regression Estimator (PCRE), r-k class estimator and r-d class estimator) and the respective predictors were considered in a misspecified linear regression model when there exists multicollinearity among explanatory variables. A generalized form was used to compare these estimators and predictors in the mean squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…According to Kayanan and Wijekoon [18], the generalized form to represent the estimators RE, AURE, LE, AULE, PCR, r−k class estimator and r−d class estimator for model ( 24) is given by γG = Gγ OLSE (26) where…”
Section: Biased Estimatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Kayanan and Wijekoon [18], the generalized form to represent the estimators RE, AURE, LE, AULE, PCR, r−k class estimator and r−d class estimator for model ( 24) is given by γG = Gγ OLSE (26) where…”
Section: Biased Estimatorsmentioning
confidence: 99%
“…Note that, γ G = γG when G = G and γ = γ, and γ G = γ * G when G = G * and γ = γ * . According to Kayanan and Wijekoon [18,25], the bias vector, dispersion matrix and MSEM of γ G can be presented as…”
Section: Stochastic Properties Of the Estimatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, Kayanan and Wijekoon [8] have shown that r-k class estimator and r-d class estimator outperformed other estimators for the selected range of regularization parameter values when multicollinearity exists among the predictor variables. However, biased estimators introduce heavy bias when the number of predictor variables is high, and the final model may contain some irrelevant predictor variables as well.…”
Section: Introductionmentioning
confidence: 99%
“…Chandra and Tyagi [4] studied the effect of misspecification due to the omission of relevant variables on the dominance of the -( , ) class estimator. Recently, Kayanan and Wijekoon [5] examined the performance of existing biased estimators and the respective predictors based on the sample information in a misspecified linear regression model without considering any prior information about regression coefficients. It is recognized that the mixed regression estimator (MRE) introduced by Theil and Goldberger [6] outperforms ordinary least squares estimator (OLSE) when the regression model is correctly specified.…”
Section: Introductionmentioning
confidence: 99%